Chemical Characteristics Of Muate Flour (Pteridophyta filicinae) As Traditional Food For The Community Of Kimaam Island - Esebius Ndumuye; Tineke M. Langi; Mercy I. R. Taroreh (Jurnal Agroekoteknologi Terapan, 2022)
Muate flour is one of the traditional foods of the people on Kimaam Island which has the Ndambu cultural tradition, namely a party to show farmers' garden products or tubers including muate flour processed from the roots of ferns. This study uses a descriptive method of laboratory experiments. which consists of 2 treatments for processing muate flour, namely A (wet method) and B (dry method). Parameters observed included yield, water content, ash content, fat content, protein and carbohydrate content. Based on the research results, muate flour has a yield: A = 60%. B= 20%. And the chemical content is A: 16.70% water, 0.50% ash, 0.79% fat, 1.92% fiber, 1.79% protein, 80.22% carbohydrates, 96.41% hydrolyzed carbohydrates. And B: 15.50% water, 3.14% ash, 0.72% fat, 3.49% fiber, 2.22% protein, 78.42% carbohydrates and 87.43% hydrolyzed carbohydrates. Keywords: Ferns, Muate Flour, Kimaam, Characteristics. Abstrak Tepung muate adalah salah satu pangan tradisional masyarakat di pulau Kimaam yang memiliki tradisi budaya Ndambu yaitu pesta untuk mempertontonkan hasil kebun petani atau umbi – umbian termasuk tepung muate olahan dari akar tumbuhan paku. Penelitian ini menggunakan metode deskriptif eksperimen laboratorium. yang terdiri dari 2 perlakuan cara pengolahan tepung muate yaitu A (cara basah) dan B (cara kering). Parameter yang diamati meliputi rendemen, kadar air, kadar abu, kadar lemak, kadar protein dan karbohidrat. Berdasarkan hasil penelitian tepung muate memiliki Rendemen: A= 60%. B= 20%. Dan kandungan kimianya yaitu A: 16.70% air, 0.50 % abu, 0.79% lemak, 1.92% serat, 1.79% protein, 80.22% karbohidrat, 96.41% karbohidrat hidrolisis. Dan B: 15.50% air, 3.14% abu, 0.72% lemak, 3.49% serat, 2.22% protein, 78.42% karbohidrat dan 87.43% karbohidrat hidrolisis. Kata Kunci: Tanaman Paku, Tepung muate, Kimaam dan Karakteristik